Academic Integrity in Selected Western Canadian Colleges and Polytechnics: A Policy Analysis - Vogt, Lisa; Eaton, Sarah Elaine; Stoesz, Brenda M.; Seeland, Josh (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2025)
Canadian colleges and polytechnics have been neglected in research on academic integrity, with some exceptions. Therefore, we examined academic integrity policy documents (N = 36) from 16 publicly-funded colleges and polytechnics in Alberta and Manitoba, Canada, replicating a qualitative research design used in previous research. Data were analyzed through the lens of five core elements of exemplary academic integrity policy. Access to policy was straightforward using the search engine present on institutional websites. In terms of approach, the three most frequently identified principles were natural justice/procedural fairness/timeliness, punitive, and ethics/integrity values/standards. The student was identified as the locus of responsibility for upholding academic integrity as a matter of student conduct, with faculty and administrators responsible for investigating and addressing misconduct after cases come to light. Within the documents, detail was extensive with plagiarism, cheating, breaches of exam integrity, collusion, falsification, fabrication, and intentional misrepresentation describing misconduct most commonly. Most documents described supports in the form of procedural steps for reporting academic misconduct, with minimal mention of proactive or remedial education. We also examined whether equity, diversity, inclusion, accessibility, decolonization, and Indigenization (EDIA-DI) were considered within these documents and found little attention was paid to these values. We call for colleges and polytechnics to update approaches to policy design that include a focus on EDIA-DI, connect academic integrity and professional ethics to educate students on institutional expectations and conduct more research to inform the development of strategies that nurture cultures of academic integrity.